Measurement Methods for the Oral Uptake of Engineered Nanomaterials from Human Dietary Sources: Summary and Outlook. Issue 4 (July 2014) - Szakal, Christopher; Tsytsikova, Lyubov; Carlander, David; Duncan, Timothy V.
Abstract This article is one of a series of 4 that report on a task of the NanoRelease Food Additive (NRFA) project of the International. Life Science Institute Center for Risk Science Innovation and Application. The project aims are to identify, evaluate, and develop methods that are needed to confidently detect, characterize, and quantify intentionally produced engineered nanomaterials (ENMs) released from food along the alimentary tract. This particular article offers an overview of the NRFA project, describing the project scope and goals, as well as the strategy by which the task group sought to achieve these goals. A condensed description of the general challenge of detecting ENMs in foods and a brief review of available and emerging methods for ENM detection is provided here, paying particular attention to the kind of information that might be desired from an analysis and the strengths and weaknesses of the various approaches that might be used to attain this information. The article concludes with an executive summary of the task group's broad findings related to the 3 topic areas, which are covered in more detail in 3 subsequent articles in this series. The end result is a thorough evaluation of the state of ENM measurement science specifically as it applies to oral uptake of ENMs from human dietary sources.